The art of computer programming : combinatorial algorithms, part I - Knuth, Donald Ervin (Boston, Massachusetts : Addision-Wesley Publishing Company, 2011)
The book is Volume 4A, because Volume 4 has itself become a multivolume undertaking. Combinatorial searching is a rich and important topic, and Knuth has too much to say about it that is new, interesting, and useful to fit into a single volume, or two, or maybe even three. This book alone includes approximately 1500 exercises, with answers for self-study, plus hundreds of useful facts that cannot be found in any other publication. Volume 4A surely belongs beside the first three volumes of this classic work in every serious programmer$1 (Bs library.s
Chapter 7-Combinatorial Searching -- Answers to Exercises -- Appendixes -- Index and Glossary.
Includes bibliographical references and index.
Keywords: ELECTRONIC DIGITAL COMPUTERS -- PROGRAMMING